ANALISIS TINGKAT PENDAPATAN PRODUKSI WINE PALA OLEH KELOMPOK TANI MAWAR DARI LAHA AGROFORESTRI DI NEGERI LILIBOOI - Petta, Jonesko; Siahaya, Troice; Wattimena, Cornelia (MARSEGU : Jurnal Sains dan Teknologi, 2024)
This research aims to determine the form of planting patterns in hamlets in Lilibooi Country, especially hamlets belonging to members of rose farmer groups and to determine the level of welfare of rose farmer group members from the production of nutmeg wine. The results of the research show that hamlets belonging to members of rose farmer groups in Lilibooi Country have an average of has a random mixture planting pattern or a random planting pattern and a combination of forestry and agricultural plants in it which is classified as an agrisilvicultural pattern. This allows the hamlet which is managed by group members to provide quite good economic value, the nutmeg yield in the hamlet is also quite good so this also influences the production of nutmeg wine which is currently being developed by the rose farmer group. The results of nutmeg wine production are also quite stable so that the profits obtained by the group are also good so that it can help the economy of the group members to improve their standard of living.